The Antihypertensive Drug Nifedipine Modulates the Metabolism of Chondrocytes and Human Bone Marrow-Derived Mesenchymal Stem Cells - Uzieliene, Ilona; Bernotiene, Eiva; Rakauskiene, Greta; Denkovskij, Jaroslav; Bagdonas, Edvardas; Mackiewicz, Zygmunt; Porvaneckas, Narunas; Kvederas, Giedrius; Mobasheri, Ali (Frontiers in Endocrinology, 2019)
Aging is associated with the development of various chronic diseases, in which both cardiovascular disorders and osteoarthritis are dominant. Currently, there is no effective treatment for osteoarthritis, whereas hypertension is often treated with L-type voltage-operated calcium channel blocking drugs, nifedipine being among the most classical ones. Although nifedipine together with other L-type voltage-operated calcium channel inhibitors plays an important role in controlling hypertension, there are unresolved questions concerning its possible effect on cartilage tissue homeostasis and the development of osteoarthritis. The aim of this study was to analyse the effects of nifedipine on metabolic processes in human chondrocytes and bone marrow mesenchymal stem cells. To better understand whether the metabolic effects are mediated specifically through L-type voltage-operated calcium channel, effects of the agonist BayK8644 were analysed in parallel. Nifedipine downregulated and mitochondrial respiration and ATP production in both cell types. Analysis of cartilage explants by electron microscopy also suggested that a small number of chondrocyte mitochondria’s lose their activity in response to nifedipine. Conversely, nifedipine enhanced glycolytic capacity in chondrocytes, suggesting that these cells have the capacity to switch from oxidative phosphorylation to glycolysis and alter their metabolic activity in response to L-type voltage-operated calcium channel inhibition. Such a metabolic switch was not observed in bone marrow mesenchymal stem cells. Nitric oxide activity was upregulated by nifedipine in bone marrow mesenchymal stem cells and particularly in chondrocytes, implying its involvement in the effects of nifedipine on metabolism in both tested cell types. Furthermore, stimulation with nifedipine resulted in elevated production of collagen type II and glycosaminoglycans in micromass cultures under chondrogenic conditions. Taken together, we conclude that the antihypertensive drug nifedipine inhibits mitochondrial respiration in both chondrocytes and bone marrow mesenchymal stem cells and that these effects may be associated with increased nitric oxide accumulation and pro-inflammatory activity. Nifedipine stimulated production of collagen type II and proteoglycans in both cell types, implying its potentially beneficial anabolic effects on articular cartilage. These results highlight a potential link between antihypertensive drugs and cartilage health.